Navigating AI Paraphrasing Tools in EFL Contexts: Investigating Quillbot’s Role in Enhancing Academic Writing Proficiency - Siti Rezky Amaliah mahmud; Muhammad Tahir; Andi Asrifan (International Journal of Language, Education, and Literature, 2026)
The use of AI-powered paraphrasing tools like QuillBot is rising among English as a Foreign Language (EFL) postgraduate students. However, its impact on holistic academic writing development remains unclear and raises concerns about dependency and academic integrity. This study aims to investigate the usage patterns, impact, perceptions, and ethical implications of QuillBot on the academic writing skills of EFL postgraduate students. Employing a sequential explanatory mixed-methods design, the study involved 24 Master's students in English Education at Universitas Negeri Makassar. Quantitative data were collected through pre-test and post-test writing assessments and questionnaires, while qualitative data were gathered from semi-structured interviews and document analysis. A paired sample t-test was used to analyze score differences, and thematic analysis was applied to qualitative data. The findings indicate that QuillBot use had a specific and significant positive effect only on improving paraphrasing skills, with no significant improvement in overall writing accuracy, fluency, or coherence. Qualitatively, students perceived QuillBot as a linguistic scaffold that enhanced efficiency and confidence but also acknowledged risks of dependency and threats to their personal academic voice. Awareness of academic integrity mediated use toward more critical and reflective practices. The study concludes that QuillBot serves as an effective aid for paraphrasing tasks but is not a substitute for higher-order writing instruction. Its integration into the curriculum requires explicit pedagogical and ethical guidance to ensure it complements rather than compromises the development of independent scholarly competence.